Summer loggings and bird protection: On regulation and derogations. Issue 2 (15th January 2019) - Pappila, Minna
Abstract : Forest loggings during the nesting season are increasing in Finland. The aim of this article is to evaluate how current regulation applies to summer loggings, paying special attention to the protection of birds. The European Union Birds Directive and the Finnish Nature Conservation Act prohibit the deliberate killing and disturbance of birds. Regardless, it seems that in practice none of these rules is applied to birds and summer loggings as forestry is not considered 'deliberate' killing or disturbance, even if thousands of birds are killed in summer loggings every year. European biodiversity targets and the principle of minimizing harms would emphasize implementing and monitoring existing national law and soft law more actively than currently is the case.